Psychological Distress in Patients having Globus Pharyngeus: A Case-Control Study - Acharya, Anup; Singh, Madan Mohan; Pokharel, Bandana (Journal of Lumbini Medical College, 2016)
Introduction: Globus sensation is described as a constant feeling of a lump or foreign body in the throat in absence of pain and dysphagia. It is a common complaint in Ear Nose and Throat clinics. Etiology of this condition remains multifactorial and unclear. Psychiatric disorder has been described as one of the cause of globus. The objective of this study is to evaluate the occurrence of psychological distress in patients complaining of globus sensation in throat coming to our centre. Methods: A case-control study was done. Patients coming to Outpatient of Ear Nose and Throat Department of Lumbini Medical College Teaching Hospital with complain of globus and not having an organic explanation of the condition were included. Age, sex and socio-economic condition matched control group was selected from healthy visitors (patient parties). Validated Nepali version of GHQ-12 was used to assess the psychological distress. Results: Psychological distress was present in 72.69% of the cases and 39.91% in the control group. The difference was statistically significant. Conclusion: Psychological distress was significantly higher in the patients with globus pharyngeus compared to the control group. It was also present in a larger fraction of the control group. The patient who present with Globus should undergo psychiatric evaluation after organic causes have been ruled out. We recommend a national policy to evaluate the population for their psychiatric health. Journal of Lumbini Medical College. 2014;2(2):45-47.